Satisfaction and Quality of Life of Families Participating in Two Different Early Intervention Models in the Same Context: A Mixed Methods Study - Verger, Sebastià; Riquelme, Inmaculada; Bagur, Sara; Paz-Lourido, Berta (Frontiers in Psychology, 2021)
Early childhood intervention is developed following different types of service organization, what requires different professional and family roles. The aim of this study was to compare the perceived satisfaction and family quality of life amongst families receiving early childhood intervention at multidisciplinar centres in comparison to those receiving routines-based early intervention at families’ homes. Under a transformative paradigm, a mixed methods design was used, using the Consumer Report Effectiveness Scale and the Beach Centre Family Quality of Life Scale and two focus groups as data collection instruments. The sample comprised 166 parents in the quantitative phase and 16 parents in the qualitative phase. Results showed that families receiving routines-based early intervention had greater satisfaction with the service although both groups showed similar scores for family quality of life in most of the analysed domains. Three dimensions were identified throughout the qualitative phase: problem solving, professional team and service organization. Both the models analyzed have an impact on family quality of life and parents are in general satisfied. Strengths and weakness were found related to the problem-solving process, the role of the professional team, family empowerment and the service’s organization. Areas for development are the effective training of professionals focused on family practices, the exchange of information with the family and the a more participatory organization taking into consideration parent’s perspectives. The given value to a combined model is another aspect highlighted in this study, as well as the need for a more agile assessment period to avoid unnecessary delays.